RNA-seq based transcriptome analysis of ethanol extract of saffron protective effect against corticosterone-induced PC12 cell injury - Xi Chen; Ting Yang; Congen Zhang; Zhijie Ma (BMC, 2022)
Abstract Background At present, oral antidepressants are commonly used in the clinical treatment of depression. However, the current drug treatment may lead to more serious adverse reactions. Therefore, we focus on Chinese traditional medicine, trying to find an effective and safe alternative or complementary medicine. Crocus sativus (saffron) is a traditional Chinese herbal medicine, which is typically used in the clinic to regulate anxiety, insomnia, amnesia, and other mental disorder. The study aimed to explore the neuroprotective effect of ethanol extract of saffron (EES) on corticosterone (CORT)- induced injury in PC12 cells and further explored its potential mechanism. Methods The authenticity of saffron and the active components of EES were identified by a water test and ultra-performance liquid chromatography-time of flight mass spectrometry system. The screening of cytotoxicity for PC12 cells was incubated with EES in different concentrations for 24 h, and the protective efficacy of EES on CORT (500 μM) -induced PC12 cell injury, cell viability was assessed by Cell Counting Kit-8 (CCK-8) assay. The differentially expressed genes (DEGs) of EES-protected PC12 cells were analyzed using the RNA-seq method, and the results were analyzed for GO and KEGG enrichment. The results of RNA-seq were verified by qPCR analysis. Results The saffron was initially identified as authentic in the water test and 10 compounds were identified by Ultra Performance Liquid Chromatography (UPLC)- Mass Spectrometry (MS). The results of CCK-8 demonstrated that EES at concentrations above 640 μg/mL exerted a certain cytotoxic effect, and PC12 cells pretreated with EES (20, 40, and 80 μg/mL) significantly reversed the 500 μM CORT-induced cell death. RNA-seq analysis showed that EES regulated 246 differential genes, which were mainly enriched in the MAPK signaling pathway. Dusp5, Dusp6, Gadd45b, Gadd45G, and Pdgfc were further validated by qPCR. Experimental data showed that the results of qPCR were consistent with RNA-seq. Conclusions These findings provide an innovative understanding of the molecular mechanism of the protective effect of EES on PC12 cells at the molecular transcription level, and Dusp5, Dusp6, Gadd45b, Gadd45g, and Pdgfc may be potential novel targets for antidepressant treatment.